THE DYNAMICS OF REYOG ART IN NGAWI REGENCY YEAR 2000-2015 - Ageng Pristiwasakti; Sumarjono Sumarjono; Bambang Soepeno (JURNAL HISTORICA, 2019)
The traditional art of Reyog originated from Ponorogo Regency spread in Ngawi Regency. Reyog Ponorogo in Ngawi District experienced fluctuation of Reyog Ponorogo Art Dynamics in Ngawi Regency needs to be done. Study as follows; (1) social condition in Kabupaten Ngawi; (2) the change of Reyog art in Ngawi District; (3) Reyog's preservation efforts in Ngawi District year 2000-2015. This method uses historical method with heuristic steps, criticism, interpretation and historiography. This study resulted Reyog art in Ngawi Regency experiencing a shift function that was originally used for ritual means to be a means of entertainment of the people in Ngawi District. The role of the Reyog artist who is incorporated in the groups in Ngawi regency has fluctuation in its preservation because of the current globalization that greatly affects the people in Ngawi regency, as well as the efforts made by the artists to keep preserving the art of Reyog. Suggestions for the future that the government, artists and society maintain and preserve this Reyog art.